An evaluation of the role of the exercise training dose for changes in exercise capacity following a standard cardiac rehabilitation program. (15th May 2023) - Iannetta, Danilo; Rouleau, Codie R.; Chirico, Daniele; Fontana, Federico Y.; Hauer, Trina; Wilton, Stephen B.; Aggarwal, Sandeep; Austford, Leslie D.; Arena, Ross; Murias, Juan M.
Abstract: Background: To retrospectively characterize and compare the dose of exercise training (ET) within a large cohort of patients demonstrating different levels of improvement in exercise capacity following a cardiac rehabilitation (CR) program. Methods: A total of 2310 patients who completed a 12-week, center-based, guidelines-informed CR program between January 2018 and December 2019 were included in the analysis. Peak metabolic equivalents (METpeak ) were determined pre- and post-CR during which total duration (ET time) and intensity [percent of heart rate peak (%HRpeak )] of supervised ET were also obtained. Training responsiveness was quantified on the basis of changes in METpeak from pre- to post-CR. A cluster analysis was performed to identity clusters demonstrating discrete levels of responsiveness (i.e., negative, low, moderate, high, and very-high ). These were compared for several baseline and ET-derived variables which were also included in a multivariable linear regression model. Results: At pre-CR, baseline METpeak was progressively lower with greater training responsiveness (F(4, 2305)  = 44.2, P < 0.01, η 2 p  = 0.71). Likewise, average training duration (F(4, 2305)  = 10.7 P < 0.01, η 2 p  = 0.02) and %HRpeak (F(4, 2305)  = 25.1 P < 0.01, η 2 p  = 0.042) quantified during onsite ET sessions were progressively greater with greater training responsiveness. The multivariable linear regression model confirmed that baseline METpeak, training duration and intensity during ET, BMI, and age (P < 0.001 ) were significant predictors of METpeak post-CR. Conclusions: Along with baseline METpeak, delta BMI, and age, the dose of ET (i.e., training duration and intensity) predicts METpeak at the conclusion of CR. A re-evaluation of current approaches for exercise intensity prescription is recommended to extend the benefits of completing CR to all patients. Highlights: Exercise training is an integral part of cardiac rehabilitation programs. Cardiorespiratory improvements following cardiac rehabilitation are variable. Intensity and total duration of exercise training predict improvements.